2007
DOI: 10.1002/ps.1460
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insecticide exposure on movement and population size estimates of predatory ground beetles (Coleoptera: Carabidae)

Abstract: BACKGROUND:Estimates of arthropod population size may paradoxically increase following insecticide applications. Research with ground beetles (Coleoptera: Carabidae) suggests that such unusual results reflect increased arthropod movement and capture in traps rather than real changes in population size. However, it is unclear whether direct (hyperactivity) or indirect (prey-mediated) mechanisms produce increased movement. RESULTS:Video tracking of Scarites quadriceps Chaudior indicated that brief exposure to la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 22 publications
4
19
1
Order By: Relevance
“…The flight tracks of pesticide‐treated Anopheles and Aedes were not significantly different from controls although the effects of pesticide exposure in changing flight behavior is well documented using video analysis in other species. Prasifka et al (2007) found after exposure to pyrethroid‐based pesticides (lambda‐cyhalothrin and tefluthrin) the carabid beetle, Scarites quadriceps (Chaudior), demonstrated an increase in total distance travelled, maximum velocity, and increased time moving. The effects of permethrin‐exposed honey bees attempting to return to their colony were similarly disrupted as they were unable to follow the visual cues and learn new directions (Cox and Wilson 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flight tracks of pesticide‐treated Anopheles and Aedes were not significantly different from controls although the effects of pesticide exposure in changing flight behavior is well documented using video analysis in other species. Prasifka et al (2007) found after exposure to pyrethroid‐based pesticides (lambda‐cyhalothrin and tefluthrin) the carabid beetle, Scarites quadriceps (Chaudior), demonstrated an increase in total distance travelled, maximum velocity, and increased time moving. The effects of permethrin‐exposed honey bees attempting to return to their colony were similarly disrupted as they were unable to follow the visual cues and learn new directions (Cox and Wilson 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Some mosquitoes may be pesticide‐resistant and others may receive a sublethal dosage of pesticide. The sublethal effects of pesticides on adult mosquitoes is not well reported, although considerable research has been conducted on larval mosquitoes (reviewed in Elliott et al 1978, Robert and Olson 1989), non‐target organisms (Newsom 1967) and beneficial insects (Delpuech et al 2001, Desneux et al 2003, Thompson 2003, Prasifka et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The behaviors of arthropods exposed to insecticides have been studied to improve the efficacy of pest management (Georghiou, 1972;Lockwood, 1984) and to preserve benefits of biodiversity such as biological pest control (Umoru et al, 1996;Rafalimanana et al, 2002;Prasifka et al, 2008). Behavioral responses of arthropods to the plant-incorporated toxins produced by insect-resistant genetically-modified (GM or transgenic) crops also have been investigated for several pest species (Harris et al, 1997 [Epiphyas postvittana (Walker)]; Ramachandran et al, 1998 [Plutella xylostella (L.)]; Parker and Luttrell, 1999 [Heliothis virescens (F.)]).…”
Section: Introductionmentioning
confidence: 99%
“…The first observable indication of intoxication in many insects treated with sub‐lethal doses of pyrethroids, including Platynus assimilis , is an increase in their LA in terms of time in movement, mean velocity and walked distance . The laboratory video tracking technique has demonstrated that brief, sub‐lethal exposures to the neurotoxic pyrethroid insecticide Fastac ® 50EC over a wide range of concentrations (0.01 to 100 mg L −1 as alpha‐cyp), may cause significant alterations in the GMA and LA of the carabid beetle Platynus assimilis .…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the fact that carabids have a great importance in plant protection as effective predators of weed seeds and many agricultural pests, sub‐lethal effects of pesticides have been rarely investigated in these insects . In fact, only in a couple of studies, sub‐lethal effects of pesticides at few doses on motor activity have been quantified in carabids using automated video‐tracking method for the measurements. Although, in general, the influence of pesticides on insect physiology and behaviour could change with time, the dynamics of sub‐lethal effects of pesticides at high, intermediate, and low doses on motor activity in short and long timescales is not specifically studied in carabids.…”
Section: Introductionmentioning
confidence: 99%